Perjudian Dalam Kerangka Hukum Ekonomi Syariah: Tinjauan Terhadap Maysir dan Konsekuensinya - Maita, Rafel; Zacharias, Vasco Javarison; Hutasoit, Tomi; M, Mahipal; Haider, Edwardo Cipta; Vahzrianur, Vehrial (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Information and communication technology has experienced very rapid development, so that the world is now borderless. Significant social changes occur rapidly through the use of internet services, which are currently used in various aspects of life, such as business, education, entertainment, social, cultural, including in Islamic practice. From the perspective of Islamic law, maysir is prohibited (haram) because it basically does not provide any benefits and brings many harms or dangers to the perpetrators. On the other hand, sharia economic law is a form of law that regulates interactions between people related to the economy, objects, and relevant legal determinations. Law Number 7 of 1974 is a positive legal product that regulates gambling. Gambling is declared a prohibited act in the Positive Law perspective, because this act not only destroys common sense but also results in other crimes such as theft, murder and fraud. This is caused by the impact of gambling which results in the perpetrator losing a way to earn money legally, thus greatly affecting economic growth in society. Therefore, it is the obligation of the Indonesian government to reduce and overcome the increase in gambling through outreach regarding the impacts and dangers of gambling, which has now spread widely in all levels of society.